Pengaruh Modal Intelektual, Ukuran Perusahaan, Dan Umur Perusahaan Terhadap Kinerja Perusahaan - Ilham Ramadhan Nasution (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the effect of intellectual capital, company size, company age on company performance on CV. Karya Pertiwi . The type of research used is quantitative method. The population in this study were all financial statements on CV. Karya Pertiwi. Based on the results of the t-test partially Intellectual Capital has a positive and significant effect on Company Performance (ROE), Company Size has no positive and significant effect on Company Performance (ROE), and Company Age has no positive and significant effect on Company Performance (ROE).